The impact of work–family conflict on early childhood teachers’ occupational well-being: the chain mediating role of psychological empowerment and job crafting - Liqun Wang; Tianqi Qiao; Xinxin Wang; Chen Wang; Pingzhi Ye (Frontiers in Public Health)
PurposeThe occupational well-being of early childhood teachers, as a crucial measure of the stability of the early childhood workforce, is increasingly becoming a core topic of interest within the education system. Work-related stressors, particularly work–family conflict, have drawn significant attention for their impact on the occupational well-being of early childhood teachers, becoming a prominent issue in the education field. However, current research rarely explores the relationship between these factors and the underlying mechanisms involved. Therefore, this study aims to investigate the relationship between work–family conflict and the occupational well-being of early childhood teachers and the mediating role of psychological empowerment and job crafting.MethodsThis study conducted a survey involving 1,200 early childhood teachers from Guangdong Province, China, using personal information forms and four scales. The collected data were processed and analyzed using SPSS 27.0.ResultsWork–family conflict showed a significant negative correlation with early childhood teacher’s occupational well-being (β = −0.268, p < 0.001). Psychological empowerment (indirect effect size = −0.049) and job crafting (indirect effect size = −0.019) partially mediated the relationship between work–family conflict and occupational well-being. Furthermore, psychological empowerment and job crafting played a chain mediating role between work–family conflict and occupational well-being (indirect effect size = −0.036).ConclusionThis study reveals the underlying mechanisms by which work–family conflict affects early childhood teachers’ occupational well-being. The findings demonstrate that work–family conflict has a direct and negative impact on the occupational well-being of early childhood teachers. Psychological empowerment and job crafting both partially mediate the relationship between work–family conflict and occupational well-being among early childhood teachers, and they also function in a serial mediating role within this association. The study provides crucial evidence supporting the significant impact of work-related stressors on early childhood teachers’ occupational well-being, serving as a reference for policymakers and educators in developing interventions targeting occupational well-being.